Repair of aortic root in patients with aneurysm or dissection: comparing the outcomes of valve-sparing root replacement with those from the Bentall procedure - Skripochnik,Edvard (2013)
INTRODUCTION: Management of aortic root aneurysm or dissection has been the subject of much discussion that has led to some modifications. The current trend is a valve-sparing root replacement. We compared the outcome following valve sparing root repair with Bentall procedure. METHODS: We retrospectively evaluated 70 patients who underwent root replacement for aneurysm or dissection and compared the outcomes of valve-sparing root replacement with those of the Bentall procedure from January 2007 to December 2011 at our institution. RESULTS: Twenty-five patients had valve-sparing aortic root replacement (VSR, including reimplantation or remodeling) (23 males and 2 females), and 45 patients had the Bentall procedure (34 males and 11 females). Patients who underwent a VSR were younger with a mean age of 55.4 ± 14.8 years compared to those who underwent the Bentall procedure with a mean age of 60.6 ± 12.7 (P=ns). The preoperative aortic insufficiency (AI) in the VSR group was moderate in 8 (32%) patients, and severe in 6 (24%). Preoperative creatinine was 1 ± 0.35 mg/dl in the VSR group and 1.1 ± 0.87 mg/dl in the Bentall group. In the VSR group, 3 (12%) patients had emergency surgery; by contrast, in the Bentall group, 8 (17%) patients had emergent surgery. Concomitant coronary artery bypass grafting (excluding coronary reimplantation) was performed in 8 (32%) patients in the VSR group and in 12 (26.6%) patients in the Bentall group (P=0.78); additional valve procedures were performed in 2 (8%) patients in the VSR group and in 11 (24.4%) patients in the Bentall group. The perioperative mortality was 8% (n=2) and 13.3% (n=6), for the VSR and Bentall procedures, respectively (P=0.7, ns). The total duration of intensive care unit stay was 116.6 ± 106 hours for VSR patients and 152.5 ± 218.2 hours for Bentall patients (P=0.5). The overall length of stay in the hospital was 10 ± 8.1 days for VSR and 11 ± 9.52 days for Bentall (P=0.89). The one-year survival was 92% for the VSR group and 79.0% for the Bentall group. The seven-year survival for the VSR group was 92% and 79% for the Bentall group (95% CI [1.215 to 0.1275], P=0.1). CONCLUSION: Aortic valve-sparing root replacement can be performed with acceptable morbidity and mortality with a comparable long-term survival to the Bentall procedure.